Financial Literacy: An Effort to Increase Students' Interest in Investment and Entrepreneurship - Hidayatul Khusnah; Riyan Sisiawan Putra; Mardiyah Anugraini; Much. Nizar Rochmatullah; Radina Fikrotuz Zakiyah; Luluk Khoiriyah (UNUSA Press, 2026)
Financial literacy is a crucial competency for students to face increasingly complex economic challenges. However, low levels of financial literacy among students often lead to consumptive behavior and a low interest in investing and entrepreneurship. Therefore, this community service activity aims to improve financial literacy and encourage investment and entrepreneurship among students at Universiti Malaysia Kelantan. The activity's implementation methods included outreach, training (workshops), interactive discussions, and evaluation through pre- and post-tests. The material covered personal financial management, an introduction to investment instruments, and the basics of entrepreneurship. The results of the activity showed a significant increase in participants' understanding of financial literacy, as well as increased student interest in investing and starting a business. Furthermore, participants also demonstrated a more positive attitude toward managing their finances wisely and productively. Therefore, this activity is expected to be a strategic effort in developing a financially independent young generation capable of contributing to economic development.